2020
DOI: 10.3892/ol.2020.11643
|View full text |Cite
|
Sign up to set email alerts
|

Application of dexmedetomidine combined with sufentanil in colon cancer resection and its effect on immune and coagulation function of patients

Abstract: Application of dexmedetomidine combined with sufentanil in colon cancer resection and its effect on immune and coagulation function of patients was studied. Colon cancer cases (n=176) admitted to Xiangya Hospital Central South University were selected into the study. They were divided into group A (n=92) and group B (n=84). In group A, patients underwent surgery anesthesia with dexmedetomidine combined with sufentanil. In group B, patients underwent surgery anesthesia only with sufentanil. The anesthesia induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…T lymphocytes play roles in perioperative immune homeostasis and tumor resistance within the digestive tract; thus, the state and subsets of T lymphocytes were investigated. Three studies, including 391 patients, investigated the effects of DEX on T lymphocytes ( 23 , 26 , 27 ). T lymphocyte subsets included were CD3+, CD4+, and CD8+ T cells.…”
Section: Resultsmentioning
confidence: 99%
“…T lymphocytes play roles in perioperative immune homeostasis and tumor resistance within the digestive tract; thus, the state and subsets of T lymphocytes were investigated. Three studies, including 391 patients, investigated the effects of DEX on T lymphocytes ( 23 , 26 , 27 ). T lymphocyte subsets included were CD3+, CD4+, and CD8+ T cells.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, sufentanil has been used to treat various cancers. Zhao et al [ 23 ] demonstrated that sufentanil improved coagulation and immune function following colon cancer resection. Tang et al [ 24 ] also confirmed that sufentanil relieves inflammatory responses after esophageal cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…DEX can improve the coagulation and immune function of patients with colon cancer, and the CD4+/CD8+ of the DEX group after surgery is higher than that of the control group ( Zhao and Li, 2020 ). DEX can reduce the immunosuppression of patients with oral cancer by increasing the percentage of CD3 + , CD4 + , DCs and CD4+/CD8+ ratio (Huang L et al, 2021).…”
Section: Dex's Regulatory Effect On Immune Cells and Inflammationmentioning
confidence: 91%